An Efficient Method for the Preparation of Sulfonamides from Sodium Sulfinates and Amines. Issue 8 (25th August 2022) - Tian, Haiying; Li, Ruiyan; Guo, Fang; Chen, Xiuling
Abstract: Sulfonamides have a special role on medicine due to their broad biological activities, as bacterial infections, diabetes mellitus, oedema, hypertension prevention and treatment. In addition, sulfonamides are also useful in herbicides and pesticides. Herein, we communicate an efficient strategy for the preparation of sulfonamides via NH4 I‐mediated amination of sodium sulfinates. This new method provides a general and environmentally friendly access to sulfonamide compounds and tolerates a wide range of functional groups. Abstract : Sulfonamides have a special role on medicine due to their broad biological activities, as bacterial infections, diabetes mellitus, oedema, hypertension prevention and treatment. In addition, sulfonamides are also useful in herbicides and pesticides. Herein, we communicate an efficient strategy for the preparation of sulfonamides via NH4 I‐mediated amination of sodium sulfinates. This new method provides a general and environmentally friendly access to sulfonamide compounds and tolerates a wide range of functional groups.